Graph-Theoretic Concepts in Computer Science 41st International Workshop, WG 2015, Garching, Germany, June 17-19, 2015, Revised Papers - Mayr, Ernst W. (Theoretical Computer Science and General Issues, 2016)
This book constitutes revised selected papers from the 41st International Workshop on Graph-Theoretic Concepts in Computer Science, WG 2015, held in Garching, Germany, in June 2015. The 32 papers presented in this volume were carefully reviewed and selected from 79 submissions. They were organized in topical sections named: invited talks; computational complexity; design and analysis; computational geometry; structural graph theory; graph drawing; and fixed parameter tractability. .